Prognostic values of left ventricular mass index progression in incident peritoneal dialysis patients : a prospective cohort study - Yun Chen; Shuqi Dai; Xiaolin Ge; Da Shang; Qionghong Xie; Chuanming Hao; Tongying Zhu (BMC Nephrology, 2022)
Abstract Background Left ventricular hypertrophy (LVH) is common among patients undergoing dialysis. However, the dynamic structural changes of LV are rarely discussed. The study aimed to investigate the prognostic significance of left ventricular mass index (LVMI)-progression in incident peritoneal dialysis (PD) patients, and explore risks factors for LVMI-progression. Methods Incident PD patients between February 2008 and July 2018 were recruited. Echocardiography was performed yearly to collect LVMI and evaluate its changes. Participants were divided into three subgroups: group with LVMI-regression, group with LVMI stable and group with LVMI-progression. The end points include all-cause mortality, cardiovascular mortality and cardiovascular events. Cox regression models were performed to identify the associations between LVMI-progression and these endpoints. Multivariate logistic regression was conducted to identify risk factors for LVMI-progression. Results A total of 216 PD patients (130 men,60.2%) with a mean age of 54.3 ± 16.8 years were recruited. LVMI-progression was identified in 72 patients (33.3%) after PD initiation. The cohort was followed for a median duration of 65.9 months. Multivariable Cox regression analysis revealed that LVMI-progression was an independent predictor of all-cause mortality (HR, 1.419; 95% CI, 1.016–1.982; p = 0.040), cardiovascular mortality (HR, 1.836; 95%CI, 1.084–3.108; p = 0.024), and cardiovascular events (HR, 1.494; 95%CI, 1.063–2.099; p = 0.021). Multivariable logistic regression showed that hemoglobin, ferritin, blood pressure and fibrinogen were significantly associated with LVMI-progression. Conclusion Early LVMI-progression was independently associated with all-cause mortality and cardiovascular outcomes in PD patients. The dynamic monitoring of LVMI might therefore help identify high-risk patients.